An Object Driven Decision Model for Quantifying the Virtual Merkus Pine Tree's Environment Contribution - Ditdit Nugeraha Utama; Bakti Amirul Jabar (HighTech and Innovation Journal)
A tree planted in the wild contributes significantly to nature and its surroundings. Key benefits include biomass production and the strengthening of soil contours. Biomass itself is a tangible output of living organisms, offering both renewable fuel potential and notable economic value. Additionally, the presence of a tree has a considerable effect on soil shear strength, which plays a crucial role in supporting reforestation efforts in deforested areas. The research aims to construct a computational decision model of a virtual Merkus Pine tree to estimate biomass production and evaluate its impact on soil reinforcement as part of the tree's environmental contributions. The model was constructed via two types of methods: an object-oriented approach for technical design and functional-structural plant modeling (FSPM) as a core method to construct a 3D virtual pine tree model. The model is a novel computational decision model operated to visually simulate the growth and development of Merkus Pine, estimate biomass yield, and calculate annual soil shear strength due to the tree’s presence. Simulation results indicate that a single Merkus Pine tree can produce up to 242.27 kg of biomass and enhance soil shear strength by approximately 0.88 N by the end of 15 years.